Determining the effectiveness of water treatment process barriers for the removal of viruses in drinking water - Setlhare, Khomotso Charity (My University, 2018)
The presence of enteric viruses in drinking water poses a health risk to consumers. It is therefore very important for drinking water suppliers to provide water that is pathogen free and fit for human consumption. This can be achieved by an effective water treatment system that ensures the safety of water from the treatment plant until the water reaches the consumer. This study assessed the ability of a conventional water treatment system to remove viruses. The system consisted of three unit processes, namely, clarification, sand filtration and disinfection. These processes were simulated on a bench-scale to determine the effectiveness of each one at removing viruses. Clarification was conducted using a Phipps and Bird jar testing system and three different chemical treatments: (i) Polyelectrolyte (SUDFLOC 3835), (ii) a combination of lime and activated silica and (iii) a combination of lime, activated silica and ferric chloride. Sand filtration was simulated using a Phipps and Bird column filtration system. Disinfection was conducted using free chlorine. The findings from this study showed that the removal or inactivation of viruses increased with an increase in the concentration of chemicals added. For clarification, the combination of lime, activated silica and ferric chloride was the most effective treatment for the removal or inactivation of viruses. Sand filtration was found to be ineffective for the removal of viruses. Disinfection was shown to be the most effective process for the removal or inactivation of viruses. While clarification, sand filtration and disinfection did not remove or inactivate viruses equally, the entire treatment chain is still essential. This is because even if a barrier does not directly remove viruses it ensures that subsequent processes can function effectively. Overall the treatment processes should not be considered as discrete barriers but rather an integrated system that must function throughout to avoid a risk to customers.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Enteric viruses; Drinking water; Water treatment; Clarification; Sand filtration; Disinfection; Dissertations, Academic -- South Africa.; Water -- Purification.; Drinking water -- Purification.